The development of the gelug school in the Amdo region in the second half of the 16th century and the construction of the Yanghua temple - Wang, Jiechen (Journal of the Belarusian State University. History, 2025)
The meeting of Altan Khan, the head of the Tumet Khanate, and Sonam Gyatso, the future Dalai Lama III, which took place on 26 May 1578, is considered. It is noted that its results were a mutually beneficial and long-term alliance between Mongols and representatives of the gelug school, the spread of Tibetan Buddhism in the area of settlement of Mongolian tribes, as well as the establishment of close relations between Mongolia and the Ming Empire. It is pointed out that the symbol of this political and religious agreement was the Yanghua temple, specially built by the Mongols in the Amdo region near lake Kukunor and the first gelug monastery in the northern regions of Tibet. The crucial role of this monastery in the history of Tibetan Buddhism is emphasised.
Keywords: Tibetan Buddhism; gelug school; Dalai Lama; Yanghua temple; Altan Khan